Comparative assessment of polycyclic aromatic hydrocarbons and their associated lifetime lung cancer at two different urban areas - Syammizam Abu Bakar (2014)
The comparative assessment of Polycyclic Aromatic Hydrocarbons in the urban atmosphere of Kota Bharu, Kelantan and Bayan Lepas, Penang was performed from January, 2010 to December, 2010. The samples were collected by using HVAS whereby the data were taken as average figures of 24-hour sample-collecting intervals. The samples were extracted with dichloromethane through ultrasonication process. The extracts were then centrifuged before being made concentrated to near dryness. 900 μl of n-hexane and 100 μl of pyrene-d₁₀ were added to the extracts to make exactly 1 ml of samples prior to being analyzed by using GC-MS. The PK() concentration at Kota Bharu and Bayan Lepas sites for the whole year of 2010 varied from 13.72 µg/m³ to 28.84 µg/m³ and 16.80 µg/m³ to 36.99 µg/m respectively. The mean concentration of individual target PAHs ranged from 0.06 ng/m³ to 0.31 ng/m³ for Kota Bharu and 0.05 ng/m3 to 0.31 ng/m³ for Bayan Lepas. From the regression results, the total PAHs and the average temperature weresignificantly negatively correlated (p<0.05) at the Bayan Lepas sampling site;besides, the Pearson partial correlation was r = -0.579. In addition, 1-1MW PAHs and Wind Speed at Kota Bharu were negatively correlated with r = -0.606 (p<0.05). Both Total PAHs at Kota Bharu and Bayan Lepas sampling sites were significantly correlated with BgP concentration (p<0.01) which is an indicator for vehicular emissions. The concentration level of Benzo(a)pyrene was within a range from 0.05 ng/m³ to 0.42 ng/m³ at Kota Bharu and within a range of 0.11 ng/m³ to 0.24 ng/m³ for Bayan Lepas. The lifetime cancer risks were identified to be higher at Kota Bharu as compared to Bayan Lepas, namely 6.64 x10⁻⁵ and 4.91 x10⁻⁵ respectively. As for the recommendation, the public should learn to reduce the usage of vehicles, especially for a short-distance journey, by using, say, bicycle. The government should set a standard allowable concentration of BaP to help maintain or even reduce the PAHs concentration in the atmosphere.